A NEW SPECIES OF PANDANUS (PANDANACEAE) FROM BINTUNI BAY, WEST PAPUA - Wiriadinata, Harry (Research Center for Biology, 2009)
WIRIADINATA, H. 2009. A new species of Pandanus (Pandanaceae) from Bintuni Bay, West Papua. Reinwardtia 12(5): 443â446. â Pandanus bintuniensis Wiriadinata collected from Bintuni Bay, West Papua is described. It is very close to P. permicron Kanehira, but differs in wider leaf and brownish green coloured young leaf.